Kahoot! As a collaborative gamified mathematics learning platform for Indonesian junior school students - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Umiatun, Kiki Nur (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
The difficulty that teachers in Indonesia face is delivering engaging lectures to raise the level of academic accomplishment among their students. Incorporating elements of the game into the educational process is one way this can be accomplished. A platform such as Kahoot! gamification may be applied to the learning process in an effective and engaging manner. The purpose of this research is to evaluate Kahoot as a learning approach that is both helpful and enjoyable for students in Indonesia, particularly during the Covid-19 pandemic. The analysis of quantitative data was involved in this investigation. The enlisted participants were 242 students. The findings of this research can be applied to the question of whether or not Kahoot! should be utilized as a teaching strategy that incorporates gamification elements to raise students' academic accomplishment. Also, one of the potential solutions to the post-pandemic would be incorporating parts of gaming into the instructional process.